PROBLEMS OF METALLOGRAPHIC DEFINITION OF OXYGEN QUANTITY IN THE DEFORMED COPPER - A. G. Anisovich (Литьë и металлургия, 2014)
Determination of oxygen amount in the deformed copper by methods of stereometric metallography is considered. The volume amount of cuprous oxide in eutectic Cu-Cu2O is determined in the program of images processing IMAGE-SP. It is shown that known value of density of cuprous oxide (6 g/cm3) doesn’t ensure possibility of the correct calculation of the structural components content. Value of 1,53 g/cm3 is determined for cuprous oxide density.